Indicators for Active Transportation in Tier II Indian Cities: A Case of Bhopal, India - Shumaila Saleem; Anuj Jaiswal (Journal of Advanced Transportation)
For a developing country to flourish sustainably, the transport sector needs to be balanced yet compete with its peers to support the growth of diverse sectors of the urban economy. Encouraging active mobility is one of the vital steps for the development of sustainable urban transportation. It indicates any mode of transport that involves physical activity, for example, cycling, walking, skateboarding and skiing. This paper is an attempt to identify the performance indicators that majorly affect the walkability and cyclability of people in cities capable of promoting active mobility. The objective is to corroborate the presence of qualitative and quantitative indicators in various sustainable transportation practices. Based on analytical hierarchy process, modified Delphi approach and user perception survey were utilised for the identification of performance indicators for Bhopal city. The indicators were segregated using exploratory factor analysis into five dimensions to categorise the performance indicators: sociodemographic, socioeconomic, physical and built environment and safety. It was found that supportive facilities were crucial for developing existing land use, physical and built environment and safety for users in a beginner city wanting to encourage users to switch to active modes choices. It was also found that urban design and built environment were the most influential factors which affect the various performance indicators for the establishment of active mobility modes for sustainable urban transportation.